THE CHOICE OF FIELDS OF STUDY: THE DIRECT AND INDIRECT EFFECTS OF FAMILY BACKGROUND - Yulia V. Kuzmina (Высшее образование в России)
This paper analyzes the relationships between family backgrounds, motivation and fieldsof study for a sample of 4-year students from Yaroslavl region and Tatarstan. The results showthat students with different family educational and material resources choose different fields of study and have different motivation. Students with high material resources and prefer to choose economic professions and rarely choose the humanities or pedagogical professions. Motivation can change the effect of family background: intensify or reduce it. Advantaged students (with high educational and material resources) explain their occupational choice by interest or job motivation and don’t follow by easiness of education or entering universities.